STRATEGI INFECTION PREVENTION CONTROL NURSE (IPCN) MEMINIMALISASI KEJADIAN TERTUSUK JARUM SUNTIK PADA PERAWAT RAWAT INAP DI RSU MITRA SEJATI MEDAN TAHUN 2020 - HESTY HERLINA OMPUSUNGGU (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
STRATEGY INFECTION PREVENTION CONTROL NURSE TO MINIMIZE THE INCIDENCE OF NEEDLE STICKING TO NURSES IN THE IN PATIENT HOSPITAL OF MITRA SEJATI MEDAN IN 2020 Hesty Herlina Ompusunggu 1, Elisabeth Dame Manalu 2, Herri Novita Tarigan3 Email : hestyherlina@gmail.com 1Masters Program Faculty Alumni of Public Health Institute of DELI HUSADA Deli Tua 2Lecture of Public Health Institute of DELI HUSADA Deli Tua Mitra Sejati General Hospital is one of the Medan North Sumatra Private Hospitals which also has an important role in health services. In terms of improving work safety especially for nurses, Mitra Sejati Hospital has made several policies such as establishing Standard Procedures Operating (SPO) before and after taking action on patients. However, there were still find the incidents the of needle sticking to nurses in the Mitra Sejati General Hospital Medan. The purpose of this study was to determine the strategy